An Analysis of IRF (Initiation-Response-Feedback) Pattern in Online English Classroom - Happy Cruzia Rini; Arina Haque (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Classroom is an environment where students and teachers can develop their communication skills. Interactions between the teacher and students in the classroom are a hallmark of communication during the teaching and learning process. Classroom activities rely heavily on interaction between students. It also affects students' academic performance. Therefore, it is essential to understand how a teacher implements classroom interaction. This study was designed to examine the types of IRF (Initiation-Response-Feedback) patterns and the most common type employed in online classroom interactions. In this pattern, there are the teacher's questions, students' responses, and the teacher's feedback. It was a descriptive qualitative study that employed classroom recording to obtain the data. The teaching and learning process involved 30 students and 1 English teacher in the online classroom. The findings revealed that all the types of IRF patterns used by the teachers and learners are procedural questions, convergent questions, divergent questions, display questions, referential questions, Socratic questions, specific response, open-ended or student-initiated, Silence, silence AV, acknowledging a correct answer, indicating an incorrect answer, praising, expanding or modifying students' answer, repeating, summary, and criticizing. This study indicated that teacher and students' initiative and response dominated the IRF pattern in this classroom. The instructor has utilized numerous types of beginning feedback. In contrast, neither work-related nor non-work-related comments were used in the discussion by students. The IRF pattern in this classroom benefited the instructor in keeping the students motivated.